2002
DOI: 10.1128/jcm.40.12.4445-4449.2002
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Virulence Factors among Clinical Isolates of Escherichia coli Causing Cystitis and Pyelonephritis in Women and Prostatitis in Men

Abstract: Differences in the presence of nine urovirulence factors among clinical isolates of Escherichia coli causing cystitis and pyelonephritis in women and prostatitis in men have been studied. Hemolysin and necrotizing factor type 1 occur significantly more frequently among isolates causing prostatitis than among those causing cystitis (P < 0.0001) or pyelonephritis (P < 0.005). Moreover, the papGIII gene occurred more frequently in E. coli isolates associated with prostatitis (27%) than in those associated with py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
101
3
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(118 citation statements)
references
References 29 publications
12
101
3
2
Order By: Relevance
“…Although there are several studies assessing E. coli virulence genes in upper UTI (5,(11)(12)(13), only one of them has been conducted in renal Tx recipients (21). We aimed to evaluate host and bacterial virulence factors mostly associated with PN by E. coli in Tx patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are several studies assessing E. coli virulence genes in upper UTI (5,(11)(12)(13), only one of them has been conducted in renal Tx recipients (21). We aimed to evaluate host and bacterial virulence factors mostly associated with PN by E. coli in Tx patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with neurogenic bladder were excluded from the sample presented here, UTI occurring in a transplanted patient is already considered as a complicated one (47) because of the heterotopic position of the graft and the shorter ureteral length. Finally, studies that observed a high prevalence of papGII in PN could have been biased by the exclusion of quinolone-resistant strains (5) because the latter would possibly possess fewer virulence factors (5,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aeruginosa is damaging to prostate tissue may be due to its sizeable genome and large repertoire of virulence factors. Epidemiological evidence has shown that bacteria require a large collection of virulence factors to establish prostate infections as compared to other urological infections such as cystitis and pyelonephritis (Ruiz et al, 2002). Furthermore, prostatitis isolates tend to be better biofilm formers than either cystitis or pyelonephritis isolates (Kanamaru et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Estudios previos han demostrado que los genes del factor citotóxico necrosante y la toxina α-hemolisina, son portados en la misma isla de patogenicidad (IP) 36 . En este estudio se detectó que 56% de las cepas presenta esta asociación, pudiendo argumentarse que las cepas de E. coli causantes de infecciones vaginales poseen algunas características de cepas necro-toxigénicas.…”
Section: Discussionunclassified